Sustained Intraocular Pressure Rise after the Treat and Extend Regimen at 3 Years: Aflibercept versus Ranibizumab - Alper Bilgic; Laurent Kodjikian; Jay Chhablani; Anand Sudhalkar; Megha Trivedi; Viraj Vasavada; Vaishali Vasavada; Shail Vasavada; Samaresh Srivastava; Deepak Bhojwani; Aditya Sudhalkar (Journal of Ophthalmology)
Purpose. To determine the risk factors associated with sustained intraocular pressure (IOP) rise in patients enrolled in the treat and extend (T&E) protocol receiving aflibercept/ranibizumab therapy for 3 years. Design. Retrospective, observational chart review. Setting. Multicentric. Patients. 789 patients (1021 eyes; 602 males) enrolled in T&E using aflibercept/ranibizumab for diabetic macular edema (DME), wet age-related macular degeneration (AMD), or macular edema in retinal vein occlusion (RVO). Intervention. The history, examination (clinical and special investigations), and treatment records were thoroughly scrutinized. Sustained IOP rise was defined as a rise in IOP above baseline by ≥6 mmHg and/or >24 mmHg on 2 or more consecutive visits. The Wilk–Shapiro test was used for confirming normality of data. The Mantel–Haenszel test and generalized estimating equations were used to analyse multicentric data as well as to analyse data from both eyes of the same patients in the event that both eyes were under therapy. The relative risk, chi-square test (with and without Yates’ correction), and univariate and multivariate analysis were used wherever appropriate. Statistical significance was set at P<0.05. The primary outcome measure was the determination of risk factors for sustained IOP rise with ranibizumab/aflibercept therapy. Secondary outcome measures included determining the incidence of IOP rise (short term and sustained), visual field, and retinal nerve fibre layer (RNFL) changes. Results. The mean follow-up was 42.4 months. Male gender, South Asian ethnicity, older age, presence of AMD and vein occlusion, use of ranibizumab, higher number of injections, narrow angles, switch to bevacizumab/ranibizumab, and preexisting glaucoma were associated with sustained IOP rise. No significant visual field and RNFL changes were seen. The overall incidence was 8.91%. No patient required filtering surgery. No patient with IOP rise returned to baseline. Conclusion. IOP rise is an important consideration as the chronicity of the condition can eventually lead to glaucomatous changes in eyes with already compromised vision. Follow-ups and use of appropriate therapy can be determined correspondingly.